EPISTEMOLOGI KEILMUAN DALAM ISLAM: KAJIAN TERHADAP PEMIKIRAN M. AMIN ABDULLAH - Musliadi Musliadi (Universitas Islam Negeri Ar-Raniry, 2014)
This article tries to answer the fundamental questions regarding epistemological problems in philosophical science discourses; the role and the influence of epistemological science in Islam and the offering constructional models of Islamic epistemological science of Amin Abdullah thinking context. Amin Abdullah is the founder of integrative-inter-connective Islamic epistemology. This integrative-inter-connective can be understood as an attempt to build a bridge knowledge of various disciplines which previously experienced a gap (normative and historical), whether religious, social, humanities, and of natural science.